ANALISIS PELANGGARAN SIARAN TELEVISI KATEGORI BERITA BERDASARKAN REGULASI KOMISI PENYIARAN INDONESIA PUSAT : Studi Kasus Pelanggaran P3SPS Oleh Media Televisi Nasional Tahun 2018-2019 - Fedrick Ivan Hasudungan Harianja (2020)
Television media has become the main broadcasting medium in Indonesian society, where television broadcasts a variety of shows, both news and entertainment to the public. Related to this, the Indonesian Broadcasting Commission acts as a supervisor and provides regulations in broadcasting in Indonesia. This research was made to explain the analysis of violations committed by various private broadcasting institutions which are supervised by the Indonesian Broadcasting Commission with one guideline, namely the Broadcasting Behavior Guidelines and Broadcast Program Standards (P3SPS), and Law Number 32 of 2002 Concerning Broadcasting. Research uses media normative theory. The research method used is a qualitative method, with the approach and nature of descriptive research. Then, for data analysis techniques in the field use case studies to be able to find out how the KPI supervision flow in monitoring the content of news broadcasts in accordance with the Broadcasting Behavior Guidelines and Broadcast Program Standards (P3SPS) in its supervision. In this study it was found that there were 15 violations that occurred in 2018, and 24 violations that occurred in 2019. The Central KPI issued a kind of written warning to broadcasters who had violated P3SPS, especially on television broadcasting in the news category. Then, during 2018-2019, the most widely violated on television news broadcast categories, namely, in P3 (Pedoman Perilaku Penyiaran) in Article 22 Paragraph (3), with a total of 26 violations. Whereas in SPS (Standar Program Siaran), the most violated was Article 43 letter (g), with a total of 9 cases.